The Reinforcement Effect of Nano-Zirconia on the Transverse Strength of Repaired Acrylic Denture Base - Mohammed Gad; Aws S. ArRejaie; Mohamed Saber Abdel-Halim; Ahmed Rahoma (International Journal of Dentistry)
Objective. The aim of this study was to evaluate the effect of incorporation of glass fiber, zirconia, and nano-zirconia on the transverse strength of repaired denture base. Materials and Methods. Eighty specimens of heat polymerized acrylic resin were prepared and randomly divided into eight groups (n=10): one intact group (control) and seven repaired groups. One group was repaired with autopolymerized resin while the other six groups were repaired using autopolymerized resin reinforced with 2 wt% or 5 wt% glass fiber, zirconia, or nano-zirconia particles. A three-point bending test was used to measure the transverse strength. The results were analyzed using SPSS and repeated measure ANOVA and post hoc least significance (LSD) test (P≤0.05). Results. Among repaired groups it was found that autopolymerized resin reinforced with 2 or 5 wt% nano-zirconia showed the highest transverse strength (P≤0.05). Repairs with autopolymerized acrylic resin reinforced with 5 wt% zirconia showed the lowest transverse strength value. There was no significant difference between the groups repaired with repair resin without reinforcement, 2 wt% zirconia, and glass fiber reinforced resin. Conclusion. Reinforcing of repair material with nano-zirconia may significantly improve the transverse strength of some fractured denture base polymers.